PENGARUH FINANCIAL DERIVATIF, LEVERAGE, TUNNELING INCENTIVE, DAN INTANGIBLE ASSET TERHADAP TRANSFER PRICING PADA PERUSAHAAN MANUFAKTUR PERIODE 2018-2021 - Arsyita Aulia Rohmah; Sartika Wulandari (Economic Faculty, University of Widya Gama Mahakam Samarinda, 2023)
Transfer pricing is a policy in setting the price of goods and services for transactions between two countries that have a special relationship. This research intends to examine the effect of financial derivatives, leverage, tunneling incentives, and intangible assets on transfer pricing. The subject of this research is a manufacturing industry that is listed on the Indonesia Stock Exchange (IDX) during the 2018-2021 period. The sampling technique in this study used purposive sampling, obtained observational information of 60 observations. The information analysis method used is panel information regression analysis using the Eviews 12 tool. The results show that (1) financial derivatives, tunneling incentives, and intangible assets have no significant effect on transfer pricing; (2) leverage has a significant effect on transfer pricing, and (3) financial derivatives, leverage, tunneling incentives, and intangible assets simultaneously have an effect on transfer pricing.